O Pantocrator de Claudio Pastro: importância e atualidade - Tommaso, Wilma Steagall de (2013)
This research explores the Pantocrator, the depiction of Christ in Glory relatively unkown in Brazil, where the barroque is the most common art religious and portrays Jesus crucified. Claudio Pastro is a Brazilian artist who has for over thirty years placed the Christ Pantocrator as a central theme in the churches he designs. The starting point was a series of interviews with the author on his background, influence and motivation towards Pantocrators. This study searched for the image of Jesus, God of the Christians and the only to be portrayed among the Abrahamic religions, although not without controversy. Later it studies the Majestas Domini, the Pantocrator from the west with major influence in the artist, achieving the representation of God with religious and political implications throughout the centuries to finally achieve contemporaneity with movements of modern art and the occurrences before and after the Second Vatican Council. The objective is to understand the meaning of the Pantocrator image in the Brazilian churches as well as the reasons why an art style from the first century reappears today